A new method of studying the soil for the presence of nematode eggs - Melnychuk , V. V. (Scientific Progress & Innovations, 2019)
The purpose of the article is to improve the method of studying the soil for the presence of nematode eggs. The task of the research was to establish in the laboratory conditions the optimal density of an improved two-component flotation solution based on inorganic salt in combination with alkali; to determine its efficiency in comparison with well-known methods of detecting nematode eggs in soil samples. Research methods. The research was conducted during 2018 on the basis of the Laboratory of Parasitology and Veterinary-Sanitary Expert Examination Department at Poltava State Agrarian Academy. A new method of detecting nematode eggs in soil samples was developed and improved, based on the methods of Romanenko (1968) and Gudzhabidze (1969), Dolbin et al. (2012), in which flotation methods with saturated salt solutions were used. The development of the new method was carried out by introducing changes in the weight of the investigated soil, the time of treating it with alkali and centrifugation procedures, as well as the composition of the flotation fluid solution, based on inorganic salt in combination with alkali. The research results. When studying the density of a new flotation solution for the purpose of detecting nematode eggs in soil samples, it has been proven that the offered solution of inorganic salt in combination with alkali (the density from 1.35 to 1.41 g/cm3) has expressed optimal flotation properties for nematode eggs (the efficiency from 48.29 % to 86.27 %). The offered method has been more effective as compared with the methods of Dolbin et al. (2012), Romanenko (1968) and Gudzhabidze (1969): in terms of time the effectiveness was 1.78 and 34.70 % (p <0.001); as to the number of nematode eggs in the soil test sample – by 24.04 % (p <0.01) and 38.66 % (p <0.001) more effective; by the number of positive samples – by 20 %. Elements of scientific novelty. A new method of soil sample testing for the presence of nematode eggs has been studied; this method is more effective and ergonomic. Practical significance. The results of the obtained data enable us to recommend the offered method for introduction into production in order to establish qualitative and quantitative indicators of contaminating environmental objects with helminthes’ eggs, as well as to predict the epizootic well-being of animals concerning nematodoses.